Effects of prosthesis-patient mismatch on cardiac function and clinical outcome after transcatheter aortic valve implantation - Parasca Catalina A.; Calin Andreea; Rosca Monica; Botezatu Simona; Enache Roxana; Beladan Carmen; Deleanu Dan; Chioncel Ovidiu; Bubenek-Turconi Serban; Iliescu Vlad A.; Popescu Bogdan A. (Sciendo, 2024)
Transcatheter aortic valve implantation (TAVI) prostheses have better hemodynamics compared to surgical prostheses, with a lower incidence of prosthesis-patient mismatch (PPM). Nonetheless, the effects of PPM have been controversial regarding clinical impact. This study aims to determine the short-term impact of PPM on cardiac function and the effect of PPM on mid-term outcome in patients undergoing transfemoral TAVI with balloon-expandable valves.